Cause of hospitalization and its outcome in patient with chronic myeloid leukemia in Patan Hospital (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Chronic Myeloid Leukemia (CML) is a myeloproliferative neoplasm characterized by dysregulated proliferation of granulocytes because of reciprocal translocation of chromosome 9 and 22. Despite the advances in treatment of CML, it still has a significant burden in patients’ life because of cost of medication, frequent hospitalization and effect on quality of life. The aim of this study is to find out the cause of hospitalization and its outcome in patient with CML.Method: It is a retrospective cross-sectional study conducted at Patan Hospital. The study included data of hospitalization of CML patients over a period of 3 years from April 2020 to April 2023 which was obtained from the record files and discharge notes of the patients. The data included information regarding age and sex of the patients, phase of disease, name of Tyrosine kinase inhibitor (TKI) used, cause of hospitalization and outcome of the hospitalization.Result: There were total of 102 admissions of which 82 admissions were analyzed. The mean age was 49 y, 56% were male, 70.7% were in chronic phase of disease and imatinib was the commonest TKI used (51.2 %). Disease related events were the most common cause of hospital admission (61%); 70 patients (85.4%) improved and were discharged whereas 12 patients (14.6 %) died during hospitalization.Conclusion: The commonest cause of hospitalization in CML patient was disease related events i.e., disease progression, drug related adverse effects and new diagnosis. Transformation to blast crisis had worst prognosis with increased mortality.